Molecular brakes based on the Zn(ii) porphyrin dimer. (27th April 2018) - Meshkov, Ivan N.; Bulach, Véronique; Gorbunova, Yulia G.; Jouaiti, Abdelaziz; Sinelshchikova, Anna A.; Kyritsakas, Nathalie; Grigoriev, Mikhail S.; Tsivadze, Aslan Yu.; Hosseini, Mir Wais
Abstract : The rotational movement of molecular brakes based on two Zn–porphyrin units interconnected by a spacer may be reversibly locked by addition of an external auxiliary ligand. Abstract : Two types of molecular brakes based on two Zn–porphyrin units interconnected by a spacer are described. Their dynamic behaviour in solution at room temperature was studied by UV-Vis spectroscopy. In the absence of an external effector, the brake undergoes free rotation, whereas in the presence of an external effector, the rotational process may be hindered. The locking/unlocking processes are shown to be reversible.